Improvement of lithium sulphur batteries with spinel MgFe2O4 and MgCr2O4 additives - Chong, Ching Hoong (Nanyang Technological University, 2021)
Lithium sulphur batteries have been of paramount interest because of its high energy density (2500 Wh/kg), high capacity for the increasingly advanced energy storage system, environmentally friendly, and low production cost. Lithium sulphur battery is the promising candidate for the next generation of high-capacity rechargeable battery. However, lithium sulphur batteries have poor cycling performance that is due to shuttling of soluble polysulfide intermediates. The lithium polysulfide is highly soluble in electrolyte commonly used for lithium sulphur batteries. This shuttle effect results in the continuous leakage of active material (sulphur) from the cathode. These obstruct the lithium sulphur battery launch to the market soon. Solution to the unresolved issues is being researched. In order to trap the polysulfides, 2 spinel oxides, Magnesioferrite (MgFe2O4) and Magnesiochromite (MgCr2O4) are used in the experiments. The spinel oxides are mixed with carbon and formed the cathode to adsorb the sulphur. Static Polysulphide Adsorption Test has been conducted to compare the adsorption capability of the spinel oxides. The results of the adsorption test shown that MgCr2O4 has weak adsorption capability for Li2S6 solution. This adsorption tests unable to conclude the adsorption capability of MgFe2O4 because the colour of the Li2S6 solution with MgFe2O4 looks darker than Control. From the results of battery testing, the battery with MgFe2O4 and MgCr2O4 additive in the cathode showed a higher initial specific capacity of 1182.4 mAh/g and 1056.9 mAh/g respectively as compared with Control which has an initial specific capacity of 1014.7 mAh/g. Among the 2 spinel oxides, the battery cell with MgFe2O4 as additive has recorded the highest specific capacity of 856.94 mAh/g after 200 charge-discharge cycles at 0.2C. The battery cell with MgFe2O4 additive has exhibited the lowest specific capacity decay per cycle of 0.138% after 200 cycles of galvanostatic charge-discharge test at 0.2C.